Asialoglycoprotein receptor 1 mediates productive uptake of N-acetylgalactosamine-conjugated and unconjugated phosphorothioate antisense oligonucleotides into liver hepatocytes. Issue 21 (23rd October 2017) - Tanowitz, Michael; Hettrick, Lisa; Revenko, Alexey; Kinberger, Garth A.; Prakash, Thazha P.; Seth, Punit P.
Abstract: Antisense oligonucleotide (ASO) therapeutics show tremendous promise for the treatment of previously intractable human diseases but to exert their effects on cellular RNA processing they must first cross the plasma membrane by endocytosis. The conjugation of ASOs to a receptor ligand can dramatically increase their entry into certain cells and tissues, as demonstrated by the implementation of N -acetylgalactosamine (GalNAc)-conjugated ASOs for Asialoglycoprotein Receptor (ASGR)-mediated uptake into liver hepatocytes. We compared the internalization and activity of GalNAc-conjugated ASOs and their parents in endogenous ASGR-expressing cells and were able to recapitulate hepatocyte ASO uptake and activity in cells engineered to heterologously express the receptor. We found that the minor receptor subunit, ASGR2, is not required for effective in vitro or in vivo uptake of GalNAc-conjugated ASO and that the major subunit, ASGR1, plays a small but significant role in the uptake of unconjugated phosphorothioate ASOs into hepatocytes. Moreover, our data demonstrates there is a large excess capacity of liver ASGR for the effective uptake of GalNAc–ASO conjugates, suggesting broad opportunities to exploit receptors with relatively moderate levels of expression.